HUBUNGAN ANTARA HARGA DIRI DAN DISIPLIN SEKOLAH DENGAN PERILAKU BULLYING PADA REMAJA - Apsari, Fitri (Jurnal Penelitian Humaniora, 2013)
The study examined the relation between self esteem and school discipline with bullying on adolescent. The participants included 81 IX?s grade students of MTsN Tinawas Nogosari. Questionnaires were used to collect the data and anova one way method and regression were used in this study to analyze and find the dynamic of all variables. Based on the calculation, correlation coeffisien was R=0,58; F regression  =25,119; p=0,0000(p>0,01). This regression measure showed that there was a significant relation between self esteem and school discipline with bullying on adolescent. Self esteem and school discipline could be a predictor for bullying. Bullying on adolescent at school was dominated by male students. Male subjects who were involved in bullying were 30,30%  and female subjects were 24,97%. Bullying at school was appropriate with the categories, which is 34,6% verbal bullying, 24,69% cyber bullying, 22,2% social bullying, and 18,5% physical bullying.